Effect of processes of cluster formation of components on mechanical and electrical properties of polymeric composite systems - Семко, Л. С.; Нікітін, Ю. О. (Proceedings of National Aviation University (archive), 2021)
A study was made of the purposeful regulation of mechanical and electro-physical properties of composites systems: polyethylene - exfoliated graphite. The contents of the composite materials changed fr m 0 up to 1 of the exfoliated graphite part. The results obtained were interpreted within the scope of he percolation theory. It has been established that, depending on the percolation process characteristic of the giwen polyethylene and exfoliated graphite cluster structure, the polymer-graphite system can have one or two critical concentration of the percolation threshold, where a sharp change in the mechanical and electro-physical properties takes place. The reinforcement effect for a specimen of the composite material has been shown to depend on exfoliated graphite content, the structure of its clusters and adhesion strength betwi en components. The results obtained basic principles of the optimal structure formation of composite mater tls were suggested to ensure low values electro-physical properties and high strength characteristics.